A Concise Enantioselective Synthesis of (−)-Ranirestat - Trost, Barry M. (2010)
[Image: see text] A concise, enantioselective synthesis of the potent aldose reductase inhibitor ranirestat (1) is reported. The synthesis was accomplished employing inexpensive, commercially available starting materials. A palladium-catalyzed asymmetric allylic alkylation (Pd-AAA) of malonate 4 was utilized as a key transformation to construct the tetrasubstituted chiral center in the target.